2020
DOI: 10.20435/inter.v21i1.2149
|View full text |Cite
|
Sign up to set email alerts
|

Saúde mental em comunidades quilombolas do Brasil: uma revisão sistemática da literatura

Abstract: O objetivo desta revisão foi identificar estudos sobre saúde mental desenvolvidos nas populações quilombolas. Os artigos foram pesquisados em três bancos de dados: Lilacs, Medline e SciELO, utilizando os seguintes descritores: “quilombola OR quilombo AND mental health OR mental disorders”. Foram selecionados oito estudos que atenderam aos critérios de inclusão. A maioria dos trabalhos apontou os indicadores sociais e econômicos como fatores associados à condição de saúde e saúde mental dos membros das comunida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 10 publications
(20 reference statements)
0
2
0
4
Order By: Relevance
“…Some studies on therapeutic itineraries in Quilombola communities have also found among traditional and collective practices, in contact with nature and in the sharing of memories, experiences that provide the promotion of health and prevention of illness (Aciole;Silva, 2021;Batista;Rocha, 2020;Fernandes, Heaist. Santos, 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on therapeutic itineraries in Quilombola communities have also found among traditional and collective practices, in contact with nature and in the sharing of memories, experiences that provide the promotion of health and prevention of illness (Aciole;Silva, 2021;Batista;Rocha, 2020;Fernandes, Heaist. Santos, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported on the precarious living conditions, the lack of access to health services, the scarcity of public policies, and lack of professionals prepared to deal with their specificities, as well as issues of racism that directly affect the health of the Quilombola population; thus exposing the effects of social inequality on health-disease processes (Batista;Rocha, 2020;Fernandes, Heaist. Santos, 2016;Freitas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Entre esas políticas, la Política Nacional de Salud Integral de la Población Negra (PNSIPN), así como la Política Nacional de Salud Integral de las Poblaciones del Campo y de la Selva (PNSIPCF) evidencian la necesidad de atender las especificidades en salud de la población remanente de quilombo ya que expresa condiciones de vida marcadas por el proceso de exclusión de la población negra brasileña y, especialmente, la está presente en el área rural (4,5) . Sin embargo, investigaciones han evidenciado fragilidades en la ejecución de intervenciones que permitan el acceso de políticas públicas por esa población (6) . Entre ellas, el acceso a la Atención Primaria en Salud no se da solo como consecuencia de las barreras geográficas en las zonas rurales, sino también por la escasez de profesionales dispuestos a vivenciar el contexto rural, falta conocimiento en cuanto a realidad y especificidades, así como la estigmatización racial que rodea a las poblaciones vulnerables (7) .…”
Section: Introductionunclassified
“…Diversos estudos apontam condições de vida precárias, falta de acesso aos serviços de saúde, escassez de políticas públicas e de profissionais preparados para lidar com suas especificidades e o racismo como questões que afetam diretamente a saúde da população quilombola. Assim, evidenciam os efeitos da desigualdade social nos processos saúde-doença (Batista;Rocha, 2020;Santos, 2016;Freitas et al, 2011).…”
Section: Introductionunclassified